Psikologi Positif dalam Budaya Kolektif Asia: Makna Kesejahteraan & Kebahagiaan - Zulfiah Khairunnisa Syarif (PSYCHONESIA: JOURNAL OF PSYCHOLOGY, 2025)
Positive psychology originally developed within Western cultures, emphasizing individual happiness and personal achievement. However, the collectivist context of Asian cultures reveals different interpretations of well-being. This study aims to explore how Western concepts of positive psychology occurred in Asian cultures and their implications for cross-cultural theory development. Using an integrative review method, 6 relevant studies were analyzed, covering Asian contexts such as Malaysia, China, Indonesia, and other regions. The review includes both quantitative and qualitative studies. Findings indicate that Asian cultures define positive psychology through social harmony, spirituality, and life balance, whereas Western cultures emphasize happiness as personal fulfillment and stable positive emotions. Despite these differences, both perspectives agree that happiness and well-being are desirable. Within Asia, variations exist such as East Asia emphasizes moral harmony and inner balance, Southeast Asia highlights spirituality and connectedness, and South Asia focuses on spiritual transcendence. These findings affirm that positive psychology is culturally contextual and should be adapted to local, collectivist values. Practically, the study encourages the development of culturally grounded positive psychology interventions that integrate social, familial, and spiritual values.